1970
DOI: 10.1126/science.167.3917.376
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Lunar Surface in Sinus Medii

Abstract: More precise and comprehensive analytical results for lunar material in Sinus Medii have been derived from the alpha-scattering experiment on Surveyor VI. The amounts of the principal constituents at this mare are approximately the same as those of constituents at Mare Tranquillitatis. The sodium contents of both maria are lower than those of terrestrial basalts. The titanium content at Sinus Medii is lower than that at Mare Tranquillitatis; this suggests important differences in detailed chemical composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Some 50 particles from a radioactive source (this time the transuranium nuclide 242Cm) and measurement of the energy distribution of these particles by means of solid-state detectors after they had been scattered by the target atoms through angles close to 180 ø (therefore the term "backscattered"). They designed instruments that flew on three Surveyor missions (Surveyor V, VI, and VII) in the years 1967 and 1968 and yielded the first complete and accurate chemical analysis of lunar soils [Turkevich et al, 1969;Franzgrote et al, 1970;Patterson et al, 1970]. In addition to the measurement of backscattered alpha particles, these instruments already contained detectors to measure the energy distribution of protons, generated by (a, p) reactions on certain medium-heavy elements (F, Na, Mg, A1, Si, S, and C1), thus enhancing their resolution capability for these elements.…”
Section: Introductionmentioning
confidence: 99%
“…Some 50 particles from a radioactive source (this time the transuranium nuclide 242Cm) and measurement of the energy distribution of these particles by means of solid-state detectors after they had been scattered by the target atoms through angles close to 180 ø (therefore the term "backscattered"). They designed instruments that flew on three Surveyor missions (Surveyor V, VI, and VII) in the years 1967 and 1968 and yielded the first complete and accurate chemical analysis of lunar soils [Turkevich et al, 1969;Franzgrote et al, 1970;Patterson et al, 1970]. In addition to the measurement of backscattered alpha particles, these instruments already contained detectors to measure the energy distribution of protons, generated by (a, p) reactions on certain medium-heavy elements (F, Na, Mg, A1, Si, S, and C1), thus enhancing their resolution capability for these elements.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the total frequency distribution graphs the mean chemical compositions of the lunar surface at the Surveyor 5, 6 and 7 sites (Turkevich et al, 1969;Franzgrote et al, 1970;Patterson et al, 1970, respectively) are also indicated. From Surveyor data it can be seen that the Surveyor 7 site near the crater Tycho is composed of a typical terra-like material, while the Surveyor 5 and 6 sites represent mare-type sites.…”
Section: Selenochemistry Area By Areamentioning
confidence: 99%